Investigating heredity (California : CyberEd [production company] [S.l.] : Biodisc [distributor], 1998)
This'true' interactive educational program includes: subject presentation, jump-presentation, interactive tutorials, pre and post testing, on-line interactive glosarry and on-line interactive help
System requirements: Windows 486/33 processor; 8 MB available RAM; S-VGA graphics; Windows 3.x, Win95, or WinNT; sound card; CD-ROM drive; mouse
Keywords: Heredity; Genetics